The intervention with the families: take care of their parental suitability, or of their demand? - Bonavita, Viviana; Brescia, Filomena; Carbone, Agostino; Gasparri, Claudio; Girardi, Donatella; Policelli, Silvia; Rastrelli, Federica; Reale, Francesca; Sacchi, Simona; Terenzi, Valentina; Carli, Renzo (Quaderni di Psicologia Clinica, 2014)
The article develops a reflection on the models of psychological intervention directed to the family and relationships that constitute it. The introduction highlights the criticality of orthopedic interventions aimed at strengthening the organization of family through expected roles and conformists cliché constructed by common sense. A dynamic seductive for those professionals with low power, as the helping professions, who find their own power prescribing the right behavior in the name of values and skills to own (eg. parenting skills, love, comprehension). The cases, reported situations where the sadistical act to evaluate the ability to be good parent is replaced by the ability to develop a clients’ problems that are faced with (adoption, evaluation, development of the parent child, homoparenthood) when the foreignness is denied.